Factors associated with performing activities of daily living in women after suffering a stroke - Andrade, Karízia Vilanova; Souza, Izabel Cristina de; Balsells, Marianne Maia Dutra; Lima, Adman Câmara Soares; Moura, Escolástica Rejane Ferreira; Aquino, Priscila de Souza (Revista da Escola de Enfermagem da USP, 2020)
Objective: To associate sociodemographic variables and risk factors for stroke to the degree of dependence for performing the activities of daily living of women of childbearing age after suffering a stroke. Method: A prospective and analytical longitudinal study conducted in three public hospitals in Fortaleza, CE, Brazil. The Modified Barthel Index was used at the time of attending the unit and 3 months after the stroke to assess the degree of disability in the performance of activities of daily living. The chi-squared and likelihood ratio tests were chosen to analyze the association between variables. Results: There were 109 women of childbearing age who participated in the study. There was an association between higher degrees of dependence in women from the interior/rural areas, with lower income and black people (p = 0.032, p = 0.043, p = 0.03, respectively). Regarding personal risk factors, there was a greater dependency in women with heart disease (p = 0.040), sedentary (p = 0.030) and alcoholics (p = 0.017). Conclusion: The results show the factors associated with higher degrees of dependence for performing activities of daily living by women of childbearing age after the occurrence of stroke.